5 - Agro-Industrial Tobacco Production and Farmers in Igboho, Oyo-North Division, Oyo State, Nigeria: by Ademola Babalola - Ademola Babalola (Africa Development, 1987)
Ademola Babalola, Lecturer, Department ot Sociology/Anthropology Obatemi Awolowo University. Ile-Ife